Predictors of biomarker changes in the pathogenesis of cardiometabolic phenotypes in combined arterial hypertension, type 2 diabetes mellitus, and obesity - I.P. Dunaieva (Mìžnarodnij Endokrinologìčnij Žurnal)
Background. Despite the accumulation of data on the diagnostic value of individual biomarkers, there is a lack of studies that integrate multivariate analysis of changes in their levels with clinical assessment of treatment in patients with combined hypertension, type 2 diabetes, and obesity. In particular, little is known about predictors of changes in these markers under the influence of combination pharmacotherapy and about their interaction with hemodynamic, metabolic, and renal parameters. The aim of the study was to assess the prognostic role of changes in the levels of biomarkers catestatin, cardiotrophin-1, β2-microglobulin, cystatin C, neutrophil gelatinase-associated lipocalin, N-terminal prohormone of brain natriuretic peptide (NT-proBNP), leptin and insulin in the formation of a favorable cardiometabolic phenotype in patients with hypertension, type 2 diabetes and obesity, as well as to identify clinical and functional predictors of their dynamics against the background of targeted pharmacotherapy. Materials and methods. A total of 250 patients were included and classified into four clinical groups based on the combination of comorbidities. The study evaluated the levels of catestatin, cardiotrophin-1, β2-microglobulin, cystatin C, neutrophil gelatinase-associated lipocalin, NT-proBNP, leptin, and insulin. Results. The analysis showed that changes in these biomarkers are closely related to structural and functional parameters of the heart and kidneys, carbohydrate and lipid metabolism, body mass index, glycemic control, and also depend on the treatment. Catestatin, cardiotrophin-1, cystatin C, NT-proBNP, β2-microglobulin, and leptin demonstrated the highest predictive value. The results indicate they may serve as predictors of myocardial remodeling, diastolic dysfunction, renal impairment, hypertrophy, and dyslipidemia. Conclusions. The study emphasizes the feasibility of integrating biomarker monitoring into routine practice for risk stratification and personalization of therapeutic approach in patients with hypertension, especially in metabolic comorbidity.